Transnational literary history? Dutch-speaking writers in Karel van het Reve’s ‘ventistic’ Geschiedenis van de Russische Literatuur [History of Russian Literature] - Dobbeleer, Michel De (Werkwinkel, 2016)
In his Geschiedenis van de Russische literatuur [History of Russian Literature, 1985] the famous Dutch Slavist and essayist Karel van het Reve, links Russian writers, such as Gavriil Derzhavin and Aleksei Pisemskii to Dutch and Flemish ones, such as Vondel and Willem Elsschot. Further on, in the chapter on Lev Tolstoi, Multatuli’s Max Havelaar is cited, although it is clear from the start that none of these Dutch-speaking authors could have had any influence on the Russian writers to whom Van het Reve devotes his colourful chapters. In this article I explore the ‘transnational’ potential of Van het Reve’s self-willed literary-historiographical approach. It turns out that Van het Reve mentions most of these Dutch-speaking authors rather to indicate – directly or indirectly - that he (dis)likes them, than to contribute to the achievements of comparative literature. Both in his choice of authors and his way of practicing literary historiography Van het Reve manifests himself as a proponent of the vent (cf. the well-known vorm of vent or manner or man discussion). Nevertheless, some of his observations could be considered as transnational constellations (in the world-literature sense of the term).